An investigation of the post-privatization firms' financial performance in Nigeria: the role of corporate governance practices - Usman, Ojonugwa; Yakubu, Umoru Adejo (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this study is to investigate the role of corporate governance practices on the post-privatization financial performance of the firms listed on the Nigerian Stock Exchange (NSE) over the period 2005-2014. Design/methodology/approach The study uses a two-step dynamic system Generalized Method of Moments (GMM) estimation technique for 27 privatized firms by considering a wide range of controlled variables such as managerial shareholdings, board composition, debt financing and stock market development. Findings The empirical result suggests that the improvement in the firms' financial performance is attributed to good corporate governance practices through effective board composition, debt financing (leverage) and stock market development. The result further shows no substantial evidence to support that managerial shareholding improves firms' financial performance. Originality/value This study contributes to the existing literature in several ways: (1) the first time that the role of corporate governance is considered in explaining the post-privatization financial performance of firms listed on the Nigerian Stock Exchange; (2) the paper applies a two-step dynamic system GMM estimation technique, proposed by Arellano and Bover (1995) and Blundell and Bond (1998) to control for the serial correlation and heterogeneity, which remain the major weaknesses of the panel data modeling in the literature.
Keywords: Nigeria; Firm financial performance; Corporate governance; Post-privatization; Two-step dynamic system GMM; G32; G34; C58